Physical, Chemical, and Microbiological Quality of Fresh Cow's Milk in Different Packaging Types During Storage - Rukmini, Ni Ketut Sri; Astiti, Ni Made Ayu Gemuh Rasa; Janurianti, Ni Made Defy (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Milk is a livestock product with high nutritional content, recognized as a source of complete and balanced nutrition for humans, as it contains essential carbohydrates, proteins, fats, minerals, and vitamins. Improper milk handling can also cause a short shelf life and low selling prices, which ultimately will also reduce the income of farmers as milk producers. Good packaging can protect the product from microbial contamination and prevent the oxidation process caused by light and oxygen. The type of packaging certainly affects the physical, chemical, and microbiological quality of fresh cow's milk during storage. The purpose of this study was to determine the physical, chemical, and microbial quality of fresh cow's milk in different packaging during storage. This study used a completely randomized design factorial pattern consisting of 2 (two) factors: the type of packaging and storage time. The observed variables were colour, pH, water content, protein content, and total microbial count. The data obtained were analyzed using ANOVA (analysis of variance); if significant results were found (P < 0.05), they were further analyzed using Duncan's multiple range test. The results showed that the type of aluminum pouch packaging was able to inhibit microbial growth due to its airtight and light-resistant properties, which allowed it to maintain temperature quality during storage. Milk packaged in aluminium packaging of size 7.6 x 104 cfu/ml, which is smaller than milk in glass and plastic bottles. Furthermore, milk packaged in aluminium has the highest protein content during storage, namely 3.302%. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3:Good Health and Well BeingSDG 12: Responsible Consumption and Production